SYNTHESIS OF CALCAREOUS NANNOFOSSIL EVENTS IN TETHYAN LOWER AND MIDDLE JURASSIC SUCCESSIONS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1999)
This paper is a synthesis of calcareous nannofossil biostratigraphy for the Lower and Middle Jurassic of the Mediterranean Province based on several sections from Northern and Central Italy. Nannofossil events were calibrated with ammonite biostratigraphy and, when necessary, ammonite-controlled sections in South East France were incorporated. Data derive from previously published biostratigraphies and unpublished data of the authors.The large data-set allowed estimates of reliability and reproducibility of single events. As a result, in the Hettangian-Bathonian interval we propose 47 main events based on diagenesis-resistant and common taxa, 17 events based on rare but ubiquitous taxa and 12 potential events requiring further investigations due to taxonomic problems and sporadic occurrence. A biostratigraphic scheme, consisting of 11 zones and 15 subzones, is proposed for the Tethyan Lower and Middle Jurassic. The proposed biostratigraphy is compared to recent schemes compiled for Portugal, Morocco, Switzerland and the Boreal Realm. Only 27 events are reproducible in various regions, but diachroneity of most events seems to derive from different ammonite biostratigraphies applied in different areas. A very high stratigraphic resolution is achieved in Italy/France for the Pliensbachian to Lower Bajocian interval. The Sinemurian and Bathonian are characterized by the lowest resolution, and very few sections with ammonite control and/or favourable lithologies are available for improvement of nannofossil biostratigraphy. This study confirms the potential of calcareous nannofossil biostratigraphy for dating Lower and Middle Jurassic successions as well as for intra- and inter-regional correlations.